Synthesis of Some Benzimidazole Derivatives and Their Antibacterial and Antifungal Activities - Kucukbay, Hasan; Durmazt, Riza; Sirecitt, Nihat; Gunalt, Selami (Asian Journal of Chemistry, 2010)
A number of new benzimidazole derivatives were synthesized by the reaction of benzimidazole with appropriate alkyl halides. The compounds synthesized were identified by 1H NMR, 13C NMR, FT-IR spectroscopic techniques and elemental analysis. All compounds studied in this work were screened for their in vitro antimicrobial activities against the standard strains i.e., Enterococcus faecalis (ATCC 29212), Staphylococcus aureus (ATCC 29213), Escherichia coli (ATCC 25922), Pseudomonas aeruginosa (ATCC 27853) and the yeasts Candida albicans and Candida tropicalis. Some of the compounds were found effective to inhibit the growth of Gram positive (E. faecalis and S. aureus) at MIC values between 50-400 μg/mL. None of the compounds exhibit antimicrobial activity against Gram negative bactreria (E. coli and P. aeruginosa) at the concentrations studied (6.25-800 μg/mL). Nine of the tested compounds showed antifungal activity with a range of the MICs between 50 and 400 μg/mL.